Development strategy to optimize the economic return of a marginal oil field: a case study of pt. Drilling sentosa - Andria Putra, Aditia; Tjendrasa, Kin (The Indonesian Journal of Business Administration, 2019)
Abstract – PT. Drilling Sentosa, an independent upstream oil and gas company, currently faces a challenge whether the development of X Field will increase the company values and survive under low oil price environment. The objective of this paper is to evaluate risk and economic value of the field and propose development strategy to optimize the economic return of the project. Business issues are analyzed using PESTEL analysis, Porter’s 5 Forces and SWOT analysis. Economic and risk evaluation are performed using deterministic discounted cash flow analysis, sensitivity analysis and monte carlo simulation. Monte carlo simulation is conducted using four uncertain input variables: oil price, production forecast, CAPEX and OPEX. Oil price and production is modeled using stochastic process of mean-reversion model and log normal distribution, respectively. While beta distribution is selected to represent the uncertainty of CAPEX and OPEX. The development strategy is proposed based on the optimum project timing that yields higher economic return. Based on DCF, the field should be abandoned at the economic limit in the eighth year. Based on the development scenario, the project is recommended to be accepted with the Net Present Value of MMUSD 4.39, Internal Rate of Return of 30% and Pay Out Time 36 months. And the maximum loss over a project life at confidence level 95% is MMUSD 7.74.Keywords: discounted cash flow analysis, marginal oil field, monte carlo simulation, sensitivity analysis